Epigenetic regulation and therapeutic strategies in ulcerative colitis - Yan, Liwei; Gu, Chao; Gao, Shanyu; Wei, Benzheng (Frontiers in Genetics, 2023)
Ulcerative colitis (UC) is an inflammatory bowel disease, and is characterized by the diffuse inflammation and ulceration in the colon and rectum mucosa, even extending to the caecum. Epigenetic modifications, including DNA methylations, histone modifications and non-coding RNAs, are implicated in the differentiation, maturation, and functional modulation of multiple immune and non-immune cell types, and are influenced and altered in various chronic inflammatory diseases, including UC. Here we review the relevant studies revealing the differential epigenetic features in UC, and summarize the current knowledge about the immunopathogenesis of UC through epigenetic regulation and inflammatory signaling networks, regarding DNA methylation, histone modification, miRNAs and lncRNAs. We also discuss the epigenetic-associated therapeutic strategies for the alleviation and treatment of UC, which will provide insights to intervene in the immunopathological process of UC in view of epigenetic regulation.